2023
DOI: 10.1186/s12889-023-15416-1
|View full text |Cite|
|
Sign up to set email alerts
|

Adverse childhood experiences and health risk behaviours among adolescents and young adults: evidence from India

Abstract: Background Adverse childhood experiences (ACEs) are traumatic and stressful events that occur in childhood. These experiences at home, school, or in the community may damage the cognitive health and emotional skills of children and adolescents. Objective The present study examines the association between Adverse childhood experiences and risky health behaviour indicators while controlling other background characteristics among boys and girls. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Studies have attributed this gendered division to higher depressive symptoms among adolescent during the post-pubertal period 49 . Further, to investigate the gendered division in the area of early sexual debut among Indian adolescents, one of our studies recently found that early sexual debut is commonplace among adolescent boys who have a reported family history of substance users 50 . Earlier, research has also found that individuals who indicated severity and frequency of maltreatment were often more prone to violent behavior, early sexual debut, and substance abuse 51 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have attributed this gendered division to higher depressive symptoms among adolescent during the post-pubertal period 49 . Further, to investigate the gendered division in the area of early sexual debut among Indian adolescents, one of our studies recently found that early sexual debut is commonplace among adolescent boys who have a reported family history of substance users 50 . Earlier, research has also found that individuals who indicated severity and frequency of maltreatment were often more prone to violent behavior, early sexual debut, and substance abuse 51 53 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are particularly important because only a few studies, thus far, have explored the association of ACEs with health outcomes among Indian populations (Fernandes et al, 2021; M. T. Kumar et al, 2019; Maurya & Maurya, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, most ACE studies have been conducted in high-income countries (Hughes et al, 2017). This area of research has received little scientific attention in low-and middle-income countries, including India (Fernandes et al, 2021;Hughes et al, 2017; M. T. Kumar et al, 2019;Maurya & Maurya, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations